The cerebrospinal fluid cytological features of tuberculous meningitis in children - Xiao YANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Background Tuberculous meningitis (TBM) is a common central nervous system (CNS) infectious disease,and is a serious threat to people's health. Due to its diverse clinical manifestations, especially atypical in infants and young children, it is easy to be misdiagnosed and can lead to high disablility rate and mortality rate. At present, cerebrospinal fluid (CSF) cytology still plays an important role in the etiological diagnosis of CNS infectious diseases. Based on the observation of CSF cytological changes of children with TBM, this study is to further understand the performance and evolution characteristics of this disease, so as to improve the ability of early diagnosis and judgment on the treatment effect. Methods Fresh CSF was collected to make smears by using cytological slide centrifugation, and apply May-Grunwald-Giemsa (MGG) staining for morphological classification. Results CSF cytology of all patients were abnormal. The average leukocyte count of children with TBM was (310.19 ± 156.26) × 106/L, and was significantly different from that of children with purulent meningitis (P = 0.000). Lymphocyte proportion of TBM group was (66.56 ± 14.08)% , and there were significant differences among different groups (P = 0.037, 0.000). Compared to children with purulent meningitis, higher proportion of monocytes (P = 0.000, 0.020) and plasma cells (P = 0.001, 0.004) were found in children with TBM and viral meningitis. The positive detection rate of plasma cells in children with TBM was higher than that in children with purulent meningitis (P = 0.001). Conclusion The CSF cytology changing characteristics of children with TBM are revealed. In the beginning the lymphocyte proportion is dominant in CSF cytology, and then different extents of mixed cellular response appear as disease develops. For children with effective treatment, the proportion of neutrophils decreases rapidly and turns to lymphocyte reaction gradually, with monocytes and plasma cells, lasting for a long time. Long-term mixed cellular response will happen in children with ineffective treatment. All in all, the CSF cytology changing characteristics are significant in clinical diagnosis and differential diagnosis of TBM in children.